Analysis of adverse drug reactions related to drug-induced renal injury based on spontaneous adverse drug reactions reporting in Malaysia 2010 – 2014 / Nurulmaya Ahmad Sa'ad - Ahmad Sa'ad, Nurulmaya (2016)
Background: In Malaysia, it has been reported that drug-induced renal injury is one of the top 10 types of adverse drug reactions (ADRs) reported in Malaysia. The incidence has increased throughout the year sand a closer view needs to be taken. To date, studies that investigate the nephrotoxicity based on the spontaneous ADR reporting database in Malaysia are very limited. Objectives: To analyse the data on spontaneous ADR reports related to drug-induced renal injuries and urinary system disorders in Malaysia from 2010 to 2014. In addition, the aims of this study also to describe the pattern of drug-induced renal injury reported in Malaysia. This study also aimed to determine the predisposing factors that lead to drug-induced renal injury. Methods: This is a retrospective study where the data was collected at Pharmacovigilance Section, Centre of Post Registration Product, National Pharmaceutical Control Bureau (NPCB). A total of 2093 ADR reports from 2010 to 2014 related to the renal disorders were extracted from the Quest 2 database, regardless of the seriousness. Reports were classified according to the World Health Organisation (WHO) criteria for causality assessment and the types of renal injury were determined according to system organ class (SOC) of urinary system disorders. Results: From the results, it was found that 1.11 drugs were recorded per report. 52% percent of the patients with the studied ADRs were women and almost 49.5% of them were Malay. Patients between 46 to 60 years old were found to be highest group of patients reported with druginduced renal injuries. It was found that there is no association between gender (P = 0.181), race (P = 0.269) and age groups (P = 0.563) and the extent of severity. 85.7% of the reports were classified as possible. Pearson chi square test showed that there is a strong association between concomitant drug groups and the extent of severity (P < 0.001). Most of cases were reported with sub-acute reaction and it was found that there is a strong association between onsets of time category and the extent of severity (P = < 0.001) where the latent onset of time has a higher occurrence of severe adverse reactions. Out of 1904 cases, face oedema was found to be at the top of the list with 60.8% of the reported cases. Diclofenac was found to be the most reported drug causing renal injuries. From the statistical analysis, it was found that the only variable which is dosage shows a significant association with the increase in the severity of reaction caused by diclofenac. Conclusion: In conclusion, this study has pointed out diclofenac as the most common drug that causes reported renal injuries besides demonstrating the trend of renal injuries due to the use of diclofenac. Although diclofenac can be considered as safe and effective therapeutic NSAIDs for the management of a variety acute and chronic condition, it has to be used with justifiable caution. Healthcare professionals should be aware of the risk for diclofenac associated renal injuries and need to screen patients appropriately for impairment risk factors before commencing diclofenac therapy.